Masa Kepemimpinan Susilo Bambang Yudhoyono: Faktor Rakyat Indonesia Memilih Kembali Pada Periode Ke-2 - Eyda Kurnia; Amalia Putri Pebryanti; Ainin Rahmadini; Najli Safira; Sri Hidayati (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
People's expectations of positive change and progress brought by a president are only sometimes met, and a charismatic and diplomatic leader is an indicator that can bring progress to the Indonesian nation. Susilo Bambang Yudhoyono is the sixth president of Indonesia whom the Indonesian people directly elected through elections in 2004 and 2009. He is a leader who can face various problems and challenges during his tenure. SBY was always active in international cooperation and made Indonesia proud in the eyes of the world. SBY's election in the elections also became a milestone for Indonesia in becoming a more democratic country. This research aims to find out what factors are behind the Indonesian people in giving trust in SBY to serve again in the second period. This research uses a case study method with a descriptive approach to search and finds the factors of the re-election of President SBY by conducting in-depth exploration using secondary data with review materials sourced from books, articles, and scientific journals that already exist and then compiled in a research result. Based on several data and research, SBY is a charismatic leader with his leadership style that is a democratic, authentic, and aggressive style that characterizes and is unique in his leadership in his 10-year term as president of the Republic of Indonesia.